KANDUNGAN LOGAM BESI (Fe) DALAM AIR DAN IKAN SEPAT (Trichogaster trichopterus Egen) DI SUNGAI YANG MELEWATI KECAMATAN GAMBUT DAN ALUH ALUH KABUPATEN BANJAR - Herlina Wati; Krisdianto Krisdianto; Rozanie Ramli (Universitas Lambung Mangkurat, 2009)
The aims of this research were to assess contents iron in water and sepat fish at all along surface rivers Kecamatan Gambut dan Aluh Aluh. Water and fish samples are collected from three station as much three sampling interval two week in Handil Malang, Tambak Sirang and Bunifah Villages. Data Physical and Chemical parameters of rives observed were water temperature, TSS, TDS, pH, DO, BOD and COD. The result of this research showed that average contents iron from water rivers in three station as much 7,40; 2,00; 0,98 mg/l were more than from water quality standard issued by the government of south Borneo province. Average contents iron in sepat fish are 0,001; 0,221; 0,001 mg/kg lower than standard quality issud by directorat Gizi.